The analysis of serum response factor expression in bone and soft tissue prostate cancer metastases. Issue 3 (February 2014) - O'Hurley, Gillian; Prencipe, Maria; Lundon, Dara; O'Neill, Amanda; Boyce, Susie; O'Grady, Anthony; Gallagher, William M.; Morrissey, Colm; Kay, Elaine W.; Watson, R. William G.
Abstract BACKGROUND Castration‐resistant prostate cancer (CRPC) represents a challenge to treat with no effective treatment options available. We recently identified serum response factor (SRF) as a key transcription factor in an in vitro model of castration resistance where we showed that SRF inhibition resulted in reduced cellular proliferation. We also demonstrated an association between SRF protein expression and CRPC in a cohort of castrate‐resistant transurethral resections of the prostate (TURPS). The mechanisms regulating the growth of CRPC bone and visceral metastases have not been explored in depth due to the paucity of patient‐related material available for analysis. In this study, we aim to evaluate SRF protein expression in prostate cancer (PCa) metastases, which has not previously been reported. METHODS AND RESULTS We evaluated the nuclear tissue expression profile of SRF by immunohistochemistry in 151 metastatic sites from 42 patients who died of advanced PCa. No relationship between SRF nuclear expression and the site of metastasis was observed (P = 0.824). However, a negative association between SRF nuclear expression in bone metastases and survival from (a) diagnosis with PCa (P = 0.005) and (b) diagnosis with CRPC (P = 0.029) was seen. These results demonstrate that SRF nuclear expression in bone metastases is associated with survival, with patients with the shortest survival showing high SRF nuclear expression and patients with the longest survival having low SRF nuclear expression. CONCLUSION Our study indicates that SRF is a key factor determining patients' survival in metastatic CRPC and therefore may represent a promising target for future therapies. Prostate 74:306–313, 2014. © 2013 Wiley Periodicals, Inc.